Pengaruh Pemberian Asam Alfa Lipoat terhadap Kadar Kolesterol Total pada Tikus Diabetes Melitus Tipe 2 - Uli Kartika Lestari Sinaga; Ismawati Ismawati; Enikarmila Asni (Fakultas Kedokteran Universitas Riau, 2017)
Hypercholesterolemia is complication in type 2 diabetes. Alpha lipoic acid (ALA) reduced total cholesterol by modulatingcholesterol synthesis pathway and reduced cholesterol biosynthesis genes expression. The goal of this research wasto investigate the prohibition of hypercholesterolemia in type 2 diabetes rat by ALA. Fifteen adult male wistar rats (2-3 months, 200-250 g body weight) were segregated into three groups (standard, type 2 diabetes and type 2 diabetes +ALA). Type 2 diabetes induced by streptozotocin 65 mg/kg and nicotinamide 110 mg/kg. ALA was given for 3 weeksafter type 2 diabetes induced.After 31 days total cholesterol of groups labelled is measured. The result showed therewas significant difference between ALA and type 2 diabetes groups (p= 0.012), and there was no significant differencebetween ALA and standard groups (p= 0.591). As the conclusion, this study proves that ALA has effects on totalcholesterol in type 2 diabetes rats.